Asymmetric cationic lipid based non-viral vectors for an efficient nucleic acid delivery. Issue 81 (16th August 2016) - Meka, Rakeshchandra R.; Godeshala, Sudhakar; Marepally, Srujan; Thorat, Ketan; Reddy Rachamalla, Hari Krishna; Dhayani, Ashish; Hiwale, Ankita; Banerjee, Rajkumar; Chaudhuri, Arabinda; Vemula, Praveen Kumar
Abstract : Cationic lipids have been extensively studied for their ability to complex with nucleic acids to condense and consequently deliver them into the cells. Abstract : Cationic lipids have been extensively studied for their ability to complex with nucleic acids to condense and consequently deliver them into the cells. However, developing safe and efficient cationic lipids for delivering nucleic acids is still an unmet challenge. Prior structure-activity investigations led to the path to understanding the lipid structure and its transfection efficiency. The trend in the transfection profiles of linker-based lipids is different from linker-less lipids. Influence of unsaturation in the hydrophobic chains has been investigated in linker-based lipids. However, in linker-less lipids, it remains unexplored. Herein, we demonstrate that the designed cationic lipidLipid S-U with an asymmetric hydrophobic core having one stearyl (18 : 0) and one oleyl chain (18 : 1) showed superior transfection efficiency compared to its symmetric counterparts, Lipid S-S (hydrophobic core comprising of two stearyl chains (18 : 0)), andLipid U-U (two oleyl chains (18 : 1)), in vitro . Mechanistic studies involving membrane fusogenicity with FACS revealed that liposomes ofLipid S-U have higher fusogenicity (89%) with B16F10 cell membrane than saturatedLipid S-S (66%) and unsaturatedLipid U-U (70%). Endosomal escape studies with confocal microscopy in HEK 293 cells revealed that lipoplexes ofLipid S-U had a higher endosomal escape and released the genetic payload in cytoplasm more efficiently than saturatedLipid S-S and unsaturatedLipid U-U . These cumulative findings support the notion that higher cellular uptake and endosomal escape resulting from fusogenic liposomes ofLipid S-U play a pivotal role in the higher transfection efficiency of asymmetricLipid S-U .